ORGANOLEPTIC AND PHYSIC-CHEMICAL ANALYSIS OF DALU PANU GULIYA - Kumara, G.U.A. (International Journal of Ayurveda and Pharma Research, 2016)
Safety and efficacy are most important factors of the drug. Standardization is a one point of safety of the drug. Controlled trials are necessary to establish efficacy of the drug. Dalu Paá¹‡u Guliya is an important traditional drug widely used for Balaroga in Sri Lankan Traditional Medical System. It is a pure herbal drug was mentioned in Sri Lankan Ayurveda Pharmacopoeia. According to the Pharmacopeia it can use for the various kind of digestive disorders like Paá¹‡u Vamana, AtÄ«sÄra, AjÄ«rá¹‡a, AgnimÄndya and UdaraÅ›Å«la in infants and children. There are no standard values for traditional and Ayurveda herbal drug preparations. Therefore efficacy of same drugs are variable for product to product. This study was aimed to prepare standard parameters for selected drug. The drug was prepared according to original preparation method and WHO standard methods. Then it was studied morphologically and was identified its organoleptic characters such as appearance, color, odor and taste using five senses. After that drug was analyzed by using standard methods according to the WHO guidelines and recommendations of Central Council for Research in Ayurveda and Siddha (CCRAS). As physic chemical properties moisture content, pH value, total ash values and fluid extractives values were identified. According to the findings, it was pill in appearance, dark brown color, aromatic odor and Tikta taste. Observed moisture content was 38.2015%, total ash value was 18.0930%, water soluble ash value was 9.4864%, acid insoluble ash value was 3.4080%, water extractive value was 30.7316% and ethanol extractive value was 18.8840%.